ANALISIS FAKTOR RESIKO PAPARAN PESTISIDA PADA KEHAMILAN DENGAN KEJADIAN BERAT BADAN LAHIR RENDAH (BBLR) DI KOTA PADANGSIDIMPUAN TAHUN 2019 - Fithri Handayani Lubis (JURNAL KESMAS DAN GIZI (JKG), 2020)
Low birth weight (LBW) is one of the main causes of infant mortality. The problem that arises is whether there is a relationship between risk factors for pesticide exposure during pregnancy and the incidence of LBW in agricultural areas. The purpose of this study was to determine the risk factors for pesticide exposure associated with LBW incidence. This research is a case control study. Subjects were divided into two groups: a case group of 25 farmers with a history of giving birth to LBW and a control group who were neighbors of case subjects without a history of giving birth to LBW, a total of 25 farmers. This research data collection using interviews and observations. Data analysis used univariate and bivariate analysis (chi square and fisher as alternatives). Research results: risk factors for exposure to pesticides that have been shown to be associated with the incidence of LBW in Padangsidimpuan, include: occupation of pregnant women related to pesticides (OR = 6,769) completeness of personal protective equipment (PPE) while doing activities in the fields (OR = 18,857) and storage pesticides (OR = 12,667). The recommended advice is to avoid work that is directly related to pesticides during pregnancy, if you have to participate in agricultural activities, pregnant women should use complete PPE.